Correlates of survival rates for 10 African ungulate populations: density, rainfall and predation - Owen-Smith, N.; Mason, D.R.; Ogutu, J. (Wiley, 2005)
Through reconciling census totals with population structure, annual survival rates were estimated for the juvenile, yearling and adult stages of 10 ungulate species over 14 years or longer in South Africa's Kruger National Park. During this period four species maintained high abundance levels, while six species declined progressively in abundance. Multiple regression models fitted to these estimates indicated that juvenile survival was sensitive to annual variability in rainfall for most of these species, especially in the dry season component, but with no density feedback apparent. Rainfall components affected adult survival in several of the declining species, while negative density dependence in adult survival was evident for three of the four species that maintained high abundance. A negative effect of past prey availability, indexing putative changes in predator abundance, on adult survival was more strongly supported statistically among the declining species than the lagged effect of prior rainfall, potentially affecting herbaceous vegetation cover and composition. The high sensitivity of juvenile survival to environmental variability among these ungulate species was consistent with the general pattern identified for large mammalian herbivores, although the absence of any survival response counteracting the density declines was surprising. The susceptibility of adult survival to environmental influences for the declining species appeared unusual and probably reflected an interaction between nutritional shortfalls and a numerical increase in lions, preying largely upon the adult segment of these species. The ungulate species that persisted at high abundance seemed resistant to effects of rainfall on food resources and evidently drove the changes in predator abundance. The sharp density effect on adult survival among these species could indicate prey switching by lions following changes in their relative availability. Findings extend past generalizations about the demographic processes underlying the population dynamics of large mammalian herbivores and reveal how the survival rates of particular population segments respond differently to environmental influences. Demographic patterns help reveal the interplay of changing resource supplies, predation pressure and population abundance on population changes.